2019
DOI: 10.1039/c9sm00901a
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of critical buckling conditions in imperfect bilayer shells through residual swelling

Abstract: We propose and investigate a minimal mechanism that makes use of differential swelling to modify the critical buckling conditions of elastic bilayer shells, as measured by the knockdown factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In particular, the geometry and placement of a dominant defect prescribe, respectively, the buckling strength and the spot where an instability localizes. Recent extensions of this concept couple geometric defects with differentially swelling [29] or magneto-responsive [30] materials to modify the knockdown factor over time. Relatedly, a more general study showed how a homogeneous natural curvature-which can be a proxy for nonmechanical stimuli like thermal expansion, changes in pH, or differential growth-acts to raise or lower the knockdown factor in spherical shells [31].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the geometry and placement of a dominant defect prescribe, respectively, the buckling strength and the spot where an instability localizes. Recent extensions of this concept couple geometric defects with differentially swelling [29] or magneto-responsive [30] materials to modify the knockdown factor over time. Relatedly, a more general study showed how a homogeneous natural curvature-which can be a proxy for nonmechanical stimuli like thermal expansion, changes in pH, or differential growth-acts to raise or lower the knockdown factor in spherical shells [31].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the geometry and placement of a dominant defect prescribe, respectively, the buckling strength and the spot where an instability localizes. Recent extensions of this concept couple geometric defects with differentially swelling [29] or magneto-responsive [30] materials to modify the knockdown factor over time. Relatedly, a more general study showed how a homogenous natural curvaturewhich can be a proxy for nonmechanical stimuli like thermal expansion, changes in pH, or differential growth -acts to raise or lower the knockdown factor in spherical shells [31].…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, a dimensional reduction procedure was performed on the 3D magneto-elastic energy, assuming a reduced kinematics for the beams and the rods based on the Kirchhoff-Love assumptions. Moreover, we have recently presented a study on magneto-active axisymmetric shells made of hard MREs in (Yan et al, 2020), where the coupling between mechanics and magnetism was leveraged to change the stability onsets of shells undergoing pressure buckling (Hutchinson and Thompson, 2018;Lee et al, 2016Lee et al, , 2019. In this study, experiments were contrasted with a magnetic shell model for axisymmetric deformation and geometrically exact strain measures (Yan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%